2020
DOI: 10.3390/cells9030704
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase III Promotes Cell Migration and Epithelial–Mesenchymal Transition in Oral Squamous Cell Carcinoma

Abstract: Epithelial–mesenchymal transition (EMT) is strongly correlated with tumor metastasis and contains several protein markers, such as E-cadherin. Carbonic anhydrase III (CA III) exhibits low carbon dioxide hydratase activity in cancer. However, the detailed mechanisms of CA III and their roles in oral cancer are still unknown. This study established a CA III-overexpressed stable clone and observed the expression of CA III protein in human SCC-9 and SAS oral cancer cell lines. The migration and invasion abilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…EMT is a process characterized by loss of cell-cell adhesion and increase migration and invasion ability. The trans-differentiation from quiescent epithelial cells into motile mesenchymal cells is essential for tumor progression [27,28]. We observed that GDF15 expression levels were negatively correlated with adhesion molecule E-cadherin levels and positively correlated with mesenchymal marker vimentin (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…EMT is a process characterized by loss of cell-cell adhesion and increase migration and invasion ability. The trans-differentiation from quiescent epithelial cells into motile mesenchymal cells is essential for tumor progression [27,28]. We observed that GDF15 expression levels were negatively correlated with adhesion molecule E-cadherin levels and positively correlated with mesenchymal marker vimentin (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…EMT is a process characterized by loss of cell-cell adhesion and increase migration and invasion ability. The trans-differentiation from quiescent epithelial cells into motile mesenchymal cells is essential for tumor progression ( 28 , 29 ). We observed that GDF15 expression levels were negatively correlated with adhesion molecule E-cadherin levels and positively correlated with mesenchymal marker vimentin ( Figure 1F ).…”
Section: Discussionmentioning
confidence: 99%
“…The capability of c ellular migration and invasion was measured as described previously [ 28 ]. Briefly, cells seeded onto the filter inserts (8-μm pores) pre-coated with or without Matrigel for the invasion assay and migration assay, respectively.…”
Section: Methodsmentioning
confidence: 99%